Chromium Bis(anthracene‐η6) Complexes – A DFT Study. Issue 6 (12th February 2018) - Türker, Lemi
Abstract : Chromium bisanthracene‐η 6 complexes are considered within the framework of density functional theory using LANL2DZ and 6‐31+G(d) basis sets and B3LYP functional. The complexation with both the same types of rings of anthracene decks (AA‐ and BB‐type complexes) and with different rings (AB‐type complex) are considered. The optimized geometries and the associated quantum chemical properties are comparatively discussed for the both types of basis sets used. LANL2DZ basis set yielded some unreasonable results. B3LYP/6‐31+G(d) level of calculations yielded the stability order as AA > BB > AB. IR spectra of AA and BB‐type complexes resemble each other. The C–H frequencies are almost the same for both of the anthracene decks, whereas they differ in the case of AB‐type complex. UV/Vis spectra of the complexes all absorb above 500 nm. AA and AB‐type complexes in contrast to BB‐type display rather complex pattern. The NICS(0) values of various rings in the complexes considered are obtained and discussed. Abstract :